Pelos caminhos do CAPS: um olhar sobre a oferta e a demanda produzidas em um serviço de saúde mental - Angel, Natalia Camargo [UNIFESP] (2017)
The Brazilian Psychiatric Reform is a process of restructuring and reorganization of mental health care in Brazil, which has been consolidated over the years and had the creation of the Centers for Psychosocial Attention (CAPS), from the perspective of deinstitutionalization. I start from the assumption that mental health care is fragmented in the different offers available in the service, due to the way it is conceived and made feasible by the public administration and the way it is put into practice in the daily practice of professionals. This research was conceived as a reference of Institutional Analysis, as concepts of analysis of implications, institute and instituted, analysis of supply and demand, and analyzers. This is an application that is based on the intention to broaden understanding, considering how different institutions involved in CAPS as mental health equipment, as well as different recipients of desires and dynamics of relationships involving professionals, users, management and society. What is the concept of organization does not suffer interference from political actions, since, in accordance with a perspective of Institutional Analysis, as described by Baremblitt (1992), the concept of institution does not end in formal organization, which carries with it its Norms and rules, but constitution in products historically constructed by a society that produces and reproduces as social relations and if instrumental in establishments and / or devices. Thus, the mental health institution goes far beyond the CAPS as an organized service, and, above all, this service in which the research took place, and brings with it a whole history of paradigms. Therefore, this equipment is constituted by a tangle of forces reflected in the actions produced by professionals. The service is organized with pre-established flows, and these flows (it applies to the service of the service and to the network) determine how relationships of the professionals themselves and these with the users, considering what we can call multiple CAPS within one, or A CAPS that allows multiple paths for professionals and users, in a multiplicity of resources for the service in its particularities. These flows served as analyzers, allowing a better understanding of the offers, and the demands that come to us. This study aimed to analyze the supply and demand of care in a CAPS III, from the understanding of the dynamics involved in the practices of professionals in the construction and effectiveness of user flows in the service, seeking to reflect on the proposal of the mental health policy And the complexity of its execution, and of what can be built with the resources available in the sphere of the real. Therefore, considering the research perspective adopted, in line with the proposal of the Professional Master's Degree, I carried out an analysis of the implication in order to understand my involvement, feelings, motivations and perceptions regarding service and research; I also tried to map the stream of users; Identify analyzing elements in the service organization in the management of demand and service provision; And to analyze the institute and the instituted in the dynamics of the organization of the service. In this sense, I have sought to look more broadly at this particular mental health service that we are studying, considering its peculiarities. I also sought to better understand the relationships between the various lines of force that constitute the service as it is at this time, in this specific context, from all the historical influences involved in its construction and maintenance. In order to characterize the demand that arrives at the service and the initial referrals, I carried out a survey of all the medical records open for a period of 11 months, from August 2015 to June 2016, in a total of 266 medical records. The data obtained in the documentary research were analyzed by means of an analysis tool described by Merhy (1997), called "flow chart analyzer of the care model of a health service". This flowchart allowed the identification of some analyzing elements that allow a better understanding of the dynamics of the service and of the